2008
DOI: 10.1258/jms.2008.007112
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in participation in flexible sigmoidoscopy screening in the UK

Abstract: Objectives The aim of the study was to examine ethnic differences in participation in colorectal cancer screening by flexible sigmoidoscopy (FS). It assessed both intentions to be screened and actual screening uptake, and considered whether demographic, health and psychosocial factors mediated the ethnic differences. The setting of this study follows a subset of participants from the UK FS Trial. Methods A postal questionnaire assessed ethnicity, demographic characteristics, health, attitudes to screening and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 29 publications
(30 reference statements)
4
45
0
Order By: Relevance
“…Although this may represent an encouraging result, a study revealed that positive intentions to undergo CRC screening did not automatically translate into actual uptake in Asians. 25 This inconsistency was a recognized occurrence relating to selfefficacy, ambivalence caused by conflicting objectives, and perceived behavioral control. Additional research into this challenging area is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Although this may represent an encouraging result, a study revealed that positive intentions to undergo CRC screening did not automatically translate into actual uptake in Asians. 25 This inconsistency was a recognized occurrence relating to selfefficacy, ambivalence caused by conflicting objectives, and perceived behavioral control. Additional research into this challenging area is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study examining screening uptake figures indicated no significant difference between AfricanCaribbean men and women and research has suggested this reluctance is not exclusive to African-Caribbean men. 10,23 Pakistani women discussed the belief that receiving cancer treatment made the cancer spread. Data from a more representative sample would be needed to confirm whether this is a commonly held belief within the community.…”
Section: Message Dissemination and Screening Location † General Practmentioning
confidence: 99%
“…This difference could not be explained by socioeconomic status (SES) or poor health. 10 One study has specifically explored barriers to FS screening in UK ethnic minority groups, adding open-ended questions to a nationwide survey of the main ethnic minority groups, known as the Ethnibus Survey. 11 While there was high interest in screening, ethnic minority groups had lower levels of CRC awareness than white British adults and embarrassment was identified as a key barrier in the ethnic minority respondents.…”
Section: Introductionmentioning
confidence: 99%
“…162,172,174,[176][177][178] An introductory question was asked to encourage or remind the participant to read the information material sent to them prior to beginning the questionnaire: 'Have you read the orange booklet, "Bowel Cancer Screening: The Facts" found inside the NHS envelope?'. The intervention group were also asked the same question in relation to the narrative leaflet.…”
Section: Methodsmentioning
confidence: 99%
“…disgust with test procedure and the belief that screening is only for those with symptoms), 172,173 hypothesising that endorsement of such barriers would decrease and quotations portraying reassurance following participation would help enhance the perceived benefit of peace of mind from doing the test. 174 …”
Section: Worktream 2 Intervention 2: Developing and Piloting A 'Narmentioning
confidence: 99%